K‐space algorithmic reconstruction (KAREN): a robust statistical methodology to separate Bragg and diffuse scattering. Issue 1 (27th January 2020) - Weng, James; Dill, Eric D.; Martin, James D.; Whitfield, Ross; Hoffmann, Christina; Ye, Feng
Abstract : A robust statistical methodology is described whereby Bragg diffraction is separated from the total scattering without altering the underlying diffuse scattering. Subsequent evaluation of the diffuse scattering by pair distribution function methods reveals unprecedented detail on the system's real structure. Abstract : Diffuse scattering occurring in the Bragg diffraction pattern of a long‐range‐ordered structure represents local deviation from the governing regular lattice. However, interpreting the real‐space structure from the diffraction pattern presents a significant challenge because of the dramatic difference in intensity between the Bragg and diffuse components of the total scattering function. In contrast to the sharp Bragg diffraction, the diffuse signal has generally been considered to be a weak expansive or continuous background signal. Herein, using 1D and 2D models, it is demonstrated that diffuse scattering in fact consists of a complex array of high‐frequency features that must not be averaged into a low‐frequency background signal. To evaluate the actual diffuse scattering effectively, an algorithm has been developed that uses robust statistics and traditional signal processing techniques to identify Bragg peaks as signal outliers which can be removed from the overall scattering data and then replaced by statistically valid fill values. This method, described as a `K‐space algorithmic reconstruction' (KAREN), can identify Bragg reflections independent of prior knowledge of a system's unit cell. KAREN does not alter any data other than that in the immediate vicinity of the Bragg reflections, and reconstructs the diffuse component surrounding the Bragg peaks without introducing discontinuities which induce Fourier ripples or artifacts from underfilling `punched' voids. The KAREN algorithm for reconstructing diffuse scattering provides demonstrably better resolution than can be obtained from previously described punch‐and‐fill methods. The superior structural resolution obtained using the KAREN method is demonstrated by evaluating the complex ordered diffuse scattering observed from the neutron diffraction of a single plastic crystal of CBr4 using pair distribution function analysis.